Perancangan Aplikasi Smart Fence Menggunakan Visual Studio Code Berbasis IOT - Harmie, Hasya Akhlaqah; Diza Dwi Putra, Rahmattian; Josi, Ahmad; Afriansyah, Riki (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The development of the Internet of Things facilitates the integration of devices with the environment by providing networking capabilities to systems. This research focuses on an IoT-based Smart Fence monitoring system that will be capable of remote monitoring and control through an Android application. The system also enables voice control, enhancing accessibility and user convenience in specific situations. The research methodology centers around quantitative methods, where the researcher collects data from the system after conducting tests. The tests yield varied results, including an average signal speed of 46.74 Mbps, an average voice recognition rate of 75%, an average system operation time (via buttons/voice) of 9.71 seconds with a success rate of 66.67%, and application Testing with an average time of 2.13 seconds and a success rate of 71.43%. Based on the system's trial results, it is observed that the system's performance can be categorized as quite good. The system encounters challenges, especially in implementing the system in English, with values indicating failures in Testing. This research is expected to improve the efficiency of IoT-based fence control and has the potential for further development to support the advancement of IoT technology.